Factors Associated with Non-Utilisation of Health Service for Childbirth in Timor-Leste: Evidence from the 2009-2010 Demographic and Health Survey - Khanal, Vishnu; Lee, Andy; Cruz, J.; Karkee, Rajendra (BioMed Central, 2014)
Background: Timor-Leste is a young developing country in Asia. Most of its infrastructure was destroyed after a long armed conflict for independence. Despite recent expansion of health facilities and investment in healthcare, maternal mortality remains high with most mothers still giving birth at home. This study investigated factors affecting the non-utilisation of health service for childbirth in the aftermath of the independence conflict. Methods: The Timor-Leste Demographic and Health Survey 2009-2010 was the latest two-stage national survey, which used validated questionnaires to obtain information from 26 clusters derived from 13 districts of the country. Factors influencing non-utilisation of health facility for childbirth were investigated using univariate and multivariable logistic regression analyses, accounting for the cluster sampling and sample weight of the survey. Results: Of the total 5986 participants included in the study, 4472 (74.8%) did not deliver their last child at a health facility. Lack of education for the mother (adjusted odds ratio (OR): 2.04; 95% confidence interval (CI) 1.56 to 2.66) and her partner (OR: 1.45; 95% CI 1.14 to 1.84), low household wealth status (OR: 5.20; 95% CI 3.93 to 6.90), and rural residence (OR: 2.83; 95% CI 2.22 to 3.66), were associated with increased likelihood of non-utilisation of health facility for childbirth. Working mothers (OR: 1.55; 95% CI 1.32 to 1.81), who had high parity (OR: 1.78; 95% CI 1.36 to 2.32) and did not attend antenatal care service (OR: 4.68; 95% CI 2.65 to 8.28) were also vulnerable for not delivering at a health facility. Conversely, the prevalence of non-utilisation of health facility for childbirth reduced with increasing number of service components received during antenatal care visits (OR: 0.72; 95% CI 0.64 to 0.80).Conclusions: Only a quarter of Timorese women delivered at a health facility. In order to reduce maternal mortality, future interventions should target disadvantaged mothers from poor families, those residing in rural areas, have higher parity but no education, and who seldom attend antenatal care service, by improving their utilisation of health facility for childbirth.